Encyclopedia industry under fire: reflections upon the monograph “Ukrainian encyclopedias in current socio-communicative challenges” (Kyiv, 2024) - Sergii Bortnyk; Sergii Segeda (Енциклопедичний Вісник України)
The Ukraine’s encyclopedia industry has faced several new challenges as a result of the current war, including funding issues, personnel shortages, and limited access to verified information sources. Based on the monograph Ukrainian Encyclopedias in Current Socio-Communicative Challenges (Kyiv, 2024), the authors examine the difficulties that the industry has encountered amidst Russian aggression. The study emphasizes the importance of encyclopedias in affirming national identity and countering harmful disinformation, including anti-Ukrainian narratives. The role of the Encyclopedia of Modern Ukraine in this process is highlighted.